Viability Status of Ancient Indigenous Paddy (Oryza sativa L.) Varieties in Malda and Neighbouring Districts of West Bengal, India - Sarkar, Anil Chandra; Roy, Somnath (International Journal of Bio-resource and Stress Management, 2023)
From time immemorial, in India, a large number of indigenous paddy (Oryza sativa L.) varieties have been cultivated as India is one of the centres of origin of paddy. But at the advent of green revolution in the middle of the last century (1960s), devastation comes down upon these indigenous varieties. Cultivators refused to cultivate these varieties due to its low yield potentiality and the number of indigenous paddy variety declined down day by day. A five years (2006-2011) survey was conducted to study and collect information and samples; classified as per their availability and acceptability to farmers. Tulaipanji, Gobindabhog, Kataribhog, Madhumalati etc. are still cultivated in small area. Kanakchur, Lalbona, Kalabona, Sete are on extinction and Sadabona, Digha, Boali, Gagoli, Barakalam are endangered. The causes of such variety status and remedial to sustain in our agriculture have also been detected. The cultivators should be convinced and the common people should be approached for consumption of ant-diabetic, anti-oxidant pectin rich indigenous rice which is very necessary for good health. Data were further analyzed and significances of ingenious paddy varieties were highlighted.